2012
DOI: 10.1002/bsl.2001
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the ‘How I Think Questionnaire’ in a Population of French‐speaking Adolescents with Externalizing Behaviors

Abstract: 'How I Think Questionnaire' (HIT) is used to measure self-serving cognitive distortions among delinquents. Previously validated on Americans, this instrument was translated, adapted and validated for French-speaking teens. To assess convergent and discriminant validity, 336 adolescents with externalizing behaviors in Québec (Canada) completed the HIT, the Self-Reported Delinquency Scale (SRD), and the Auto-aggression Questionnaire. There were 165 boys and 171 girls with M(age) = 16.4 years (SD = 0.5) who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…This is the case for the EQUIP program, which consists in educating moral judgment, pro-social abilities and how to improve errors in the way of thinking, and aims to diminish anti-social behaviour by treating cognitive distortions of juvenile offenders (Gibbs, Potter, & Goldstein, 1995). The original version of the HIT questionnaire is in English and has been translated and adapted in various languages, such as Spanish, http://dx.doi.org/10.15405/epsbs.2018.06.29 Corresponding Author: Alina S. Rusu Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 243 Dutch and French (Nas et al, 2008;Plante et al, 2012;Fernández et. al., 2013).…”
Section: The How I Think Questionnaire (Hit; Barriga Et Al 2001)mentioning
confidence: 99%
“…This is the case for the EQUIP program, which consists in educating moral judgment, pro-social abilities and how to improve errors in the way of thinking, and aims to diminish anti-social behaviour by treating cognitive distortions of juvenile offenders (Gibbs, Potter, & Goldstein, 1995). The original version of the HIT questionnaire is in English and has been translated and adapted in various languages, such as Spanish, http://dx.doi.org/10.15405/epsbs.2018.06.29 Corresponding Author: Alina S. Rusu Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 243 Dutch and French (Nas et al, 2008;Plante et al, 2012;Fernández et. al., 2013).…”
Section: The How I Think Questionnaire (Hit; Barriga Et Al 2001)mentioning
confidence: 99%
“…While the HIT was developed for use with adolescents within the United States, it has been translated into several different languages, including Dutch (Nas, Brugman, & Koops, 2008), French (Plante et al, 2012;Van Leeuwen, Chauchard, Chabrol, & Gibbs, 2013), Italian (Bacchini, De Angelis, Affuso, & Brugman, 2015), Spanish (Fernández, Rodríguez, & Gibbs, 2013) and Swedish (Wallinius, Johansson, Larden, & Dernevik, 2011), and the reliability and validity of the HIT has been consistently favourable, bearing in mind that Wallinius et al (2011) suggested an alternative factor solution for the HIT, as compared to the one reported by the original authors (Barriga et al, 2001).…”
Section: Hit-ids Questionnairementioning
confidence: 99%
“…Validation studies conducted in different Western countries have demonstrated that the HIT-Q is a valid and reliable measure of self-serving cognitive distortions (Barriga et al, 2001; Barriga & Gibbs, 1996; Gini & Pozzoli, 2013; Nas et al, 2008; Plante et al, 2012; Van Leeuwen, Chauchard, Chabrol, & Gibbs, 2013; Wallinius et al, 2011). With respect to the factorial structure of the questionnaire, researchers have obtained different results in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, analyzing concurrent validity emerged that the HIT-Q scales correlated positively with different measures of involvement in antisocial behavior (Barriga & Gibbs, 1996; Barriga et al, 2001; Nas et al, 2008; Plante et al, 2012; Van Leeuwen et al, 2013; Wallinius et al, 2011) proactive and reactive aggression, biases at some social information processing steps, attitude toward delinquent behavior, punishment-based moral orientation (Nas et al, 2008). On the other hand, the HIT-Q scales showed negative correlations with biases at some social information–processing steps, moral reasoning (in some samples no correlation was found), victim-based moral orientation, moral atmosphere, social skills, and social desirability (Nas et al, 2008; Plante et al, 2012). No correlation was found with age, socioeconomic status (SES), intelligence, and academic achievements (Barriga et al, 2001) except that in the Swedish and Dutch samples, age and intelligence, respectively, were found to be negatively correlated with the HIT-Q score (Wallinius et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation